Business-to-business marketing - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (Los Angeles : SAGE, 2014)
This text covers both the theory and practice of business-to-business (B2B) marketing from a European perspective in a globalised world. This edition includes: More coverage of digital marketing and social media in relation to B2B ; More coverage of issues relating to sustainability and corporate social responsibility ; More visual features and an update of the B2B Snapshots ; New international examples and case studies including Zara, eBay, DHL, LinkedIn, and the horsemeat scandal ; Includes more extensive online resources including full lecturer materials and further materials for students including web links, links to SAGE journal articles, exam questions and a quizes. The text is relevant to all students taking a university module in B2B marketing at undergraduate or postgraduate levels. It will also be relevant to researchers and practitioners in the area of B2B marketing.
Machine generated contents note: pt. I Fundamentals of Business-to-Business Marketing -- 1.Business-to-Business Markets and Marketing -- 2.Buyer Behaviour -- 3.Inter-Firm Relationships and Networks -- pt. II Business-to-Business Marketing Analysis and Strategy -- 4.Responsible Business-to-Business Strategy -- 5.Researching Business-to-Business Markets -- 6.Business Market Segmentation -- pt. III Communicating and Interacting with Customers -- 7.Market Communication -- 8.Relationship Communication -- 9.Relationship Portfolios and Key Account Management -- pt. IV Managing Marketing Processes -- 10.Managing Product Offerings -- 11.Routes to Market -- 12.Price-Setting in Business-to-Business Markets.
Includes bibliographical references (pages 355-373) and index.
Keywords: Industrial marketing; Industrial marketing -- Case studies; Industrial marketing; Business-to-Business-Marketing.; Marketing; Case studies